Contribuições da ACIEPE histórias infantis e matemática na perspectiva de egressas do curso de pedagogia - Souza, Ana Paula Gestoso de (Universidade Federal de São Carlos, 2012)
In the literature related to the area of teacher formation, currently recommends the formation of reflective practitioners and researchers of their own practice embedded in a social, historical and political context. Besides, we emphasize the demand for formation environments that maintain the idea of unity between theory and practice and between teaching and research, which prioritize the development of reflection and articulation with the reality of school. Several formation courses seek to set up as a space for professional growth that does not negligence the demands of educational practice and hence follow its development. One of these environments is materializes in Curricular Activity Teaching Research and Extension (ACIEPE), called "Children's Stories and Mathematics in Initial Grade", offered since 2004, by Federal University of São Carlos. The target people of this ACIEPE are students of Pedagogy course and graduation in Mathematics and teacher of elementary school and pre-school education. Altogether, this activity includes several moments that aim: the study of references that address the primary language, the mathematical language, the potential of reading, mathematics teaching, the connection between children's literature and mathematics; the analysis of paradidatic books; the analysis of teaching and learning situations that uses infant texts and mathematics; as well as moments that result in the construction and subsequent implementation of infant books to teach mathematical content. This is the scenario that this research try to identify and analyze, from the perspective of egresses of the Pedagogy course, the contributions of ACIEPE "Children's Stories and mathematics in the elementary school" for the development of the process of learning how to teach mathematics. The theoretical framework is permeated by concepts such as: initial formation, formation of teachers that teach mathematics, knowledge base for teaching, reading and writing in math classes, the relationship between theory and practice, and others. We chose the case study of ACIEPE once the participants composes this case with their stories, highlighting their origins, direct and indirect influences, near and far. We analyzed multiple data sources - many written records that were produced over this research, teaching and extension as reports, classes plans, field diaries, books produced, etc., interview and questionnaires answered after the end of ACIEPE - enabling the data triangulation, since the variety of sources of evidence assisted in performing various analyzes of a given process. The results of this work allow us to configure the ACIEPE "Children's Stories for the elementary school" as an instance of formative teachers, because the contributions of the curricular activities for the development of the teacher in personal and professional dimension were verified of egresses who participated. Among the contributions of ACIEPE stands out the possibility that the licensees are aware of the processes of teaching and learning and understand specifically how to work them, so this activity of teaching, research and extension enables the construction of pedagogical content knowledge, the center of the knowledge base for teaching. It was found also that the dynamics involving the construction and use of a material in a collaborative group were the main sources of learning. In this formation process the institutional dimension is crucial as in the University, as forming instancy, recognizes, honors and promotes the achievement of this type of formation which showed prolific to the teacher professional development.
Keywords: Professores - formação; Aprendizagem docente; Desenvolvimento profissional; Formação inicial; Literatura infantojuvenil e matemática; Didática; Teacher learning; Professional Development; Initial education of teachers; Child Literature and Mathematics; Didactics; CIENCIAS HUMANAS::EDUCACAO